Revisiting Agnostic PAC Learning - Hanneke, Steve; Larsen, Kasper Green; Zhivotovskiy, Nikita (Proceedings / annual Symposium on Foundations of Computer Science, 2024)
PAC learning, dating back to Valiant'84 and Vapnik and Chervonenkis'64,'74, is a classic model for studying supervised learning. In the agnostic setting, we have access to a hypothesis set H and a training set of labeled samples drawn i,i d . from an unknown data distribution D. The goal is to produce a classifier that is competitive with the hypothesis in H having the least probability of mispredicting the label of a new sample from D. Empirical Risk Minimization (ERM) is a natural learning algorithm, where one simply outputs the hypothesis from H making the fewest mistakes on the training data. This simple algorithm is known to have an optimal error in terms of the VC-dimension of H and the number of samples. In this work, we revisit agnostic PAC learning and first show that ERM and any other proper learning algorithm is in fact sub-optimal if we treat the performance of the best hypothesis in H , as a parameter. We then complement this lower bound with the first learning algorithm achieving an optimal error. Our algorithm introduces several new ideas that we hope may find further applications in learning theory.